Neuroactive Drug Interactions in Geriatric Neurology: Integrating Pharmacokinetic Vulnerability, Pharmacodynamic Sensitivity, and Rational Prescribing Strategies - Purbasari, Bethasiwi (Syntax Literate, 2025)
Older adults with neurological disorders represent one of the most vulnerable populations to drug–drug interactions due to polypharmacy, age-related physiological changes, and increased sensitivity of the central nervous system. Understanding how pharmacokinetic and pharmacodynamic alterations shape the clinical behavior of neuroactive medications is essential for optimizing therapeutic decisions in this population. This narrative review synthesizes current evidence on clinically significant drug–drug interactions relevant to neurological practice in the elderly and outlines rational prescribing strategies that integrate explicit criteria, deprescribing frameworks, and age-related risk factors. A targeted literature review was conducted using peer-reviewed studies, clinical guidelines, and pharmacology databases, focusing on interactions involving antiepileptic drugs, antiparkinsonian agents, antidepressants, antipsychotics, antiplatelets, anticoagulants, and other commonly co-prescribed medications in older adults. Aging affects every component of pharmacokinetics—slowed gastrointestinal absorption, altered body composition, reduced hepatic metabolism, and diminished renal clearance—leading to higher and more variable exposure to many neuroactive drugs. Parallel changes in pharmacodynamics, including weakened blood–brain barrier integrity and altered neurotransmitter receptor sensitivity, amplify the risk of adverse neurological outcomes such as delirium, imbalance, falls, worsening motor symptoms, or cognitive decline. High-impact interactions were identified in epilepsy (enzyme-inducing ASMs and DOACs), Parkinson’s disease (dopaminergic therapy and antipsychotics), post-stroke care (clopidogrel–PPI and serotonergic combinations), and dementia (cholinesterase inhibitors and anticholinergics). Rational prescribing requires medication review, application of Beers 2023 and STOPP/START v3 criteria, careful dose adjustment, structured deprescribing, and close monitoring. Effective management of neuroactive pharmacotherapy in older adults depends on integrating mechanistic understanding of age-related PK/PD vulnerability with individualized prescribing and deprescribing strategies. A systematic, patient-centered approach can reduce interaction-related harms while preserving neurological stability and quality of life.